iPSC-Derived Natural Killer Cell Therapies - Expansion and Targeting - Goldenson, Benjamin H.; Hor, Pooja; Kaufman, Dan S. (Frontiers in Immunology, 2022)
Treatment of cancer with allogeneic natural killer (NK) cell therapies has seen rapid development, especially use against hematologic malignancies. Clinical trials of NK cell-based adoptive transfer to treat relapsed or refractory malignancies have used peripheral blood, umbilical cord blood and pluripotent stem cell-derived NK cells, with each approach is undergoing continued clinical development. Improving the potency of these therapies relies on genetic modifications to improve tumor targeting and to enhance expansion and persistence of the NK cells. Induced pluripotent stem cell (iPSC)-derived NK cells allow for routine targeted introduction of genetic modifications and expansion of the resulting NK cells derived from a clonal starting cell population. In this review, we discuss and summarize recent important advances in the development of new iPSC-derived NK cell therapies, with a focus on improved targeting of cancer. We then discuss improvements in methods to expand iPSC-derived NK cells and how persistence of iPSC-NK cells can be enhanced. Finally, we describe how these advances may combine in future NK cell-based therapy products for the treatment of both hematologic malignancies and solid tumors.